Spatial analysis of congenital syphilis in the State of Rio Grande do Norte, between 2008 and 2018 - Dhyanine Morais de Lima Raimundo; George Jó Bezerra Sousa; Ana Beatriz Pereira da Silva; Romanniny Hévillyn Silva Costa Almino; Nanete Carolina da Costa Prado; Richardson Augusto Rosendo da Silva (SciELO, 2021)
ABSTRACT Objective: To analyze the spatial distribution of congenital syphilis cases in a state in northeastern Brazil. Method: This is an ecological study, with secondary data for the period from 2008 to 2018, taking as a sample the notified cases of congenital syphilis in Rio Grande do Norte. In the data analysis, the eight health regions of the state were used as units of analysis, and the local and global Moran's I was performed, with subsequent smoothing through the local empirical Bayesian method, which resulted in thematic maps. Results: The results showed an increase in cases of congenital syphilis in the 3rd and 7thhealth regions. In terms of spatial analysis, this investigation showed clusters in the 3rd, 5th, and 7thhealth regions, with an increased risk for congenital syphilis of up to 2.65 times and with an incidence rate of 7.91 cases per 1,000 live births. Conclusion: The spatial analysis of congenital syphilis cases allowed observing a high incidence in some health regions, with averages above those calculated for the entire state, indicating the need to implement effective strategies to achieve its control.